The - Janda, Kenneth (Houghton Mifflin, 2008)
This best-selling, mainstream American government text is both a comprehensive introduction and a complete program, with the print text and ancillaries carefully crafted to work together to benefit both instructor and student. The Ninth Edition maintains its highly acclaimed, non-ideological framework, exploring three themes: freedom, order, and equality as political values; the majoritarianism vs. pluralism debate; and globalization's effect on American politics. Extensively updated, this edition includes new examples, figures, and data and current discussions on such topics as the 2006 Congressional election, the Bush administration, campaign finance reform, Hurricane Katrina and FEMA, immigration policy, MEDICARE, and more.Continuing to offer leading-edge technology for teaching and learning, the program now offers course content in Eduspace, Blackboard, and WebCT formats. Additional media tools include the new In Our Own Words feature--downloadable chapter overviews in MP3 format narrated by the authors--and marginal references to the award-winning site, IDEAlog.org